Evaluation of Beach Ecosystems in Monta District, Bima Regency Using Macroalgae as an Indicator of Marine Tourism Development - Sukarni; Hartati; Nikman Azmin (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to evaluate the condition of coastal ecosystems in Monta District, Bima Regency, to support the development of conservation-based marine tourism. Macroalgae were employed as bioindicators due to their high sensitivity to changes in water quality. The research applied quantitative descriptive design through field surveys and laboratory analyses at six coastal sites: Sarae Me’e, Woro, Soro, Wilamaci, Tanjung, and Pasir Putih. Data collection was carried out using the transect-quadrat method to identify macroalgal species, alongside measurements of environmental parameters including temperature, pH, salinity, DO, nitrate, and orthophosphate. Data were analyzed using the Shannon-Wiener Diversity Index (H′), ANOVA, and Pearson correlation to examine differences and relationships among parameters. The results demonstrated that macroalgae effectively serve as bioindicators for assessing coastal ecosystem conditions. Barrang Caddi Island was found to have healthier ecological conditions with a diversity index (H′) of 2.42, a uniformity index of 0.76, a low nitrate concentration of 0.03 mg/l, and a dominance index of 0.22. In contrast, Barrang Lompo Island, with the highest nitrate and BOD levels, was categorized as lightly polluted. In general, ecosystems with higher biodiversity, even species distribution, and lower nutrient concentrations tend to be more stable and resilient. These findings provide a scientific basis for sustainable coastal management, promote the use of macroalgae as a cost-effective monitoring tool, and support environmentally friendly marine tourism and conservation initiatives.